Development of E-Learning Materials Assisted by Augmented Reality in the Science Subject of Water Cycle Material for Grade V Elementary Schools - Dwika Yafi Muharromi; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop, test the feasibility, effectiveness, and practicality of Augmented Reality (AR)-assisted e-learning materials to improve student learning outcomes. This study is a development research (R&D) using the Borg and Gall model. This study involved 34 fifth-grade students of SDN Dampyak 02 in the 2024/2025 academic year, with a small-scale trial on 12 VA-class students and a large-scale trial on 22 VB-class students. The feasibility of e-learning materials is shown from the results of validation by material, language, and media experts which showed that AR-assisted e-learning materials were declared "feasible" with an average score of 78%. The practicality of e-teaching materials is shown from the results of the questionnaire responses of teachers and students to the use of e-teaching materials assisted by AR showing a "very positive" level of satisfaction with a score of 88% from teachers and 88% from students. The effectiveness of e-teaching materials assisted by AR is proven through the results of the t-test with a significance value of 0.000 (<0.05) and an N-gain of 0.6, which is included in the "moderate" category. The results of the study indicate that e-teaching materials assisted by AR meet the criteria of being feasible, practical, and effective in improving learning outcomes in science learning for grade V at SD Negeri Dampyak 02.